2020
DOI: 10.1002/yea.3522
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing in the yeast Nakaseomyces delphensis and description of its complete sexual cycle

Abstract: The environmental yeast Nakaseomyces delphensis is, phylogenetically, the closest known species to Candida glabrata, a major fungal pathogen of humans. C. glabrata is haploid and described as asexual, while N. delphensis is also haploid, but has been described as competent for mating and meiosis. Both genomes contain homologues of all the genes necessary for sexual reproduction and also the genes for Ho‐dependent mating‐type switching, like Saccharomyces cerevisiae. We first report the construction of genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The collection of papers in this Special Issue include basic science studies focusing on features of the life cycles of yeasts. A paper by Zhou Li, Boisnard, Enache‐Angoulvant, and Fairhead (2020) compared the life cycle of the wild yeast Nakaseomyces delphensis with that of the laboratory yeast S. cerevisiae . Surprisingly, the authors found that, unlike S. cerevisiae , which is largely diploid, N. delphensis exists predominantly in the haploid state.…”
mentioning
confidence: 99%
“…The collection of papers in this Special Issue include basic science studies focusing on features of the life cycles of yeasts. A paper by Zhou Li, Boisnard, Enache‐Angoulvant, and Fairhead (2020) compared the life cycle of the wild yeast Nakaseomyces delphensis with that of the laboratory yeast S. cerevisiae . Surprisingly, the authors found that, unlike S. cerevisiae , which is largely diploid, N. delphensis exists predominantly in the haploid state.…”
mentioning
confidence: 99%